A Teenager With Sacroileitis, Rash and Fever Caused by Streptobacillus moniliformis Bacteremia. Issue 12 (December 2016) - Gill, Navneet K.; Craft, David; Crook, Tonya; Dossett, John
Abstract : We report a rare case of sacroileitis in a teenager resulting from Streptobacillus moniliformis bacteremia, identified by matrix-assisted laser desorption/ionization-time of flight. We discuss the challenges of making this diagnosis and review the literature on rat bite fever.